مسئلہ کشمیر اور پاکستان کی آبی سلامتی:تحقیقی و تجزیاتی مطالعہ: Kasmir Issue and Pakistan’s Water Security: A Research-Based and Analytical Study (Al-Qamar, 2025)
The Kashmir conflict, a longstanding geopolitical dispute between Pakistan and India, carries far-reaching implications beyond territorial sovereignty, prominently impacting Pakistan’s water security. This research paper presents a comprehensive analytical study on the hydrological dimensions of the Kashmir issue, examining how Indian control over upstream water sources especially within Indian administered Jammu and Kashmir affects Pakistan’s water flow under the framework of the Indus Water Treaty (IWT) of 1960. While the treaty allocates three western rivers (Indus, Jhelum, and Chenab) to Pakistan, India’s infrastructural interventions such as dam constructions, hydroelectric projects, and water diversion strategies pose significant threats to the timely and sufficient flow of water to Pakistan’s agricultural and domestic sectors. Employing qualitative and quantitative research methodologies, the study critically reviews official reports, legal frameworks, water usage data, and satellite imagery to assess the extent and consequences of upstream developments. It explores the nexus between hydro-politics and national security, highlighting the vulnerability of Pakistan’s economy largely dependent on irrigation-based agriculture to Indian water control. Moreover, the study discusses international legal precedents, bilateral disputes under the IWT, and potential avenues for diplomatic or multilateral resolution. The study concludes that the Kashmir issue critically affects Pakistan’s water security and sustainability. It urges Pakistan to adopt proactive water diplomacy, strengthen internal infrastructure, and engage with international forums.
Keywords: Kashmir Conflict, Indus Waters Treaty, Water Security